2013
DOI: 10.1037/a0030867
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical human face processing? Evidence from masked priming.

Abstract: Face processing without awareness might depend on subcortical structures (retino-collicular projection), cortical structures, or a combination of the two. The present study was designed to tease apart these possibilities. Because the retino-collicular projection is more sensitive to low spatial frequencies, we used masked (subliminal) face prime images that were spatially low-pass filtered, or high-pass filtered. The masked primes were presented in the periphery prior to clearly visible target faces. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
3
31
1
Order By: Relevance
“…Finally, the authors examined the influence of face processing without awareness while our task examined overt face comparison, and these might involve different neural substrates. It is not so clear, therefore, that our findings are at odds with those of Khalid et al (2012), and further consideration for the apparent differences is warranted.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Finally, the authors examined the influence of face processing without awareness while our task examined overt face comparison, and these might involve different neural substrates. It is not so clear, therefore, that our findings are at odds with those of Khalid et al (2012), and further consideration for the apparent differences is warranted.…”
Section: Discussionmentioning
confidence: 69%
“…On the surface, this claim seems to be inconsistent with some existing findings. For example, Khalid, Finkbeiner, König, and Ansorge (2012) demonstrated that low-pass (but not high-pass) filtered face primes presented peripherally produce a congruency effect in a sex discrimination task; that is, performance was enhanced when the preceding prime and following probe were of the same gender compared with when they were not. This finding seems to suggest that information about the sex of a face may be subcortically represented, contrary to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These behavioral studies suggest that gender information is processed in the subcortical visual system that plays a major role in infants. Furthermore, a behavioral study has reported that the priming of masked (subliminal) spatially low-pass, but not high-pass, filtered facial images significantly affected the subsequent discrimination of gender (Khalid et al, 2013). Because subliminal low-pass filtered images are thought to be processed in the subcortical visual pathway (Tamietto and de Gelder, 2010), these findings suggest that the subcortical pathway can process gender information (Khalid et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These subcortical routes might also be involved in the rapid processing of facial expression information (Morris et al, 2001; Tamietto and de Gelder, 2010), and the facial detection of infants with immature cortical visual systems might depend on the subcortical visual system (Johnson, 2005). Furthermore, human neuropsychological studies have reported substantial evidence that suggests that this subcortical pathway is involved in the discrimination of face gender and facial identity (Morris et al, 2001; Khalid et al, 2013; Gabay et al, 2014). Consistently, recent neurophysiological studies have reported that neurons in the monkey SC and pulvinar respond differentially to various photos of human and monkey faces, human facial expressions, and face-like patterns (Maior et al, 2010; Van Le et al, 2013; Nguyen et al, 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%